Readiness to teacher education program: the role of academic performance as an entry-level of future educators - Jessa A. Roman; Adriel G. Roman (Intelektual Pustaka Media Utama, 2026)
Higher academic performance during the senior high school program and passing marks in the qualifying examination are the two major requirements before an aspirant tertiary student is admitted to a teacher education program. However, questions have been raised on the performance of teacher education graduates in the Licensure examination, which in the past decade, obtained a low national passing percentage. Given the scenario, is the entry-level requirement sufficient, or does it need further enhancement? This study correlates the academic performance during high school of 273 aspirant education students with their qualifying examination scores. A descriptive–correlational design was used. Results show that aspirant students’ academic performance during senior high school is in outstanding level. However, it does not match their entrance examination results in the three main components of the examination for teacher education students, namely: general education, professional education, and major field of specialization. For this reason, it is concluded that obtaining high academic records during high school does not guarantee obtaining a high entrance examination rating. Finally, several recommendations are offered after the conduct of the study.